Serum growth differentiation factor 15 as a biomarker for malnutrition in patients with acute exacerbation of chronic obstructive pulmonary disease - Shi, Guifen; Yue, Longfei; Tang, Zhengying; Wang, Yingling; Hu, Xiwei; Tong, Yufeng (Frontiers in Nutrition, 2024)
Background: COPD is a common respiratory disease that often coexists with malnutrition during acute exacerbation (AECOPD) and significantly affects the prognosis. Previous studies have shown that GDF15 levels promote appetite suppression, weight loss, and muscle weakness, and are sharply elevated in peripheral blood following inflammatory stimulation. However, whether serum GDF15 levels can be used to predict malnutrition in patients with AECOPD remains unknown.Methods: A total of 142 patients admitted to the Department of Respiratory Medicine at Anshun People's Hospital between December 2022 and August 2023 were selected for the study. The participants were divided into two groups: malnutrition group (n=44) and non-malnutrition group (n=98) based on a BMI< 18.5 kg/m2 , according to the GLIM criteria. Serum GDF15 levels were measured using the ELISA. Spearman correlation analysis was employed to examine the association between serum GDF15 levels, baseline data, and clinical indicators. Binary logistic regression was utilized to identify the independent risk factors for AECOPD combined with malnutrition. The predictive value of serum GDF15, ALB, and a combination of these in identifying malnutrition in patients with AECOPD was evaluated using a ROC curve.Results: In this study, the serum levels of GDF15 in patients with malnutrition and AECOPD were significantly higher than those in patients without malnutrition, whereas the serum ALB levels were significantly lower than those in patients without malnutrition. Moreover, the serum GDF15 levels were negatively correlated with BMI , MAC,CC, TP, ALB, and PNI, and positively correlated with CRP, CAT score, mMRC classification, and GOLD grade. Furthermore, the serum levels of GDF15 were an independent risk factor for malnutrition in patients with AECOPD. The optimal cutoff value of serum GDF15 level and ALB leve were 1092.885pg/mL and 36.15g/L, with a sensitivity of 65.90%, 86.40% and specificity of 89.80%, 65.00%, as well as a combined sensitivity of 84.10% and a specificity of 73.90%. The serum GDF15 and serum ALB levels demonstrated a good predictive ability, and the ROC revealed a greater combined prediction value (AUC=0.935).Serum GDF15 levels could be used as a potential biomarker for predicting malnutrition in patients with AECOPD, offering guidance for future clinical evaluations of malnutrition.